The global energy transition: challenges and opportunities – a perspective from North America - T. Koning (Georesursy, 2024)
The energy transition from fossil fuels to renewables is dominating the news in North America and other parts of the world. A decade ago, most people would have viewed global warming as an academic subject which did not impact themselves nor warrant serious concern. However, currently many parts of the world are experiencing record temperatures and related environmental impact such as the extensive forest fires being experienced in the western USA and Canada. Accordingly, governments worldwide recognize the need for future economic activity to be carbon-neutral or as is also termed carbon-zero. To achieve the goal of carbon-neutral economies by 2050 will be hugely challenging but economic opportunities will also arise in the major development of solar, wind and geothermal energy.